2018
DOI: 10.17305/bjbms.2018.3371
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of breast cancer metastasis risk using circulating tumor markers: A follow-up study

Abstract: Distant organ tumor dissemination is a major cause of breast cancer-related deaths. In 2010, we analyzed the prognostic importance of the circulating tumor markers (CTMs) cytokeratin 19 (CK19), CK20, epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor 2 (HER2) in relation to the clinical and pathological characteristics of patients with breast cancer (BC). To assess the clinical utility of CK19, CK20 and EGFR in predicting distant metastasis in BC, here we report 7-year follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The reduction of the risk of breast cancer metastasis may have a great improvement in survival outcomes of breast cancer patients [50][51][52]. If we can get the probability of breast cancer metastasis before it occurs and take some measures to deal with it, the patients may have a better survival outcome and a high quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of the risk of breast cancer metastasis may have a great improvement in survival outcomes of breast cancer patients [50][51][52]. If we can get the probability of breast cancer metastasis before it occurs and take some measures to deal with it, the patients may have a better survival outcome and a high quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been reports that examined the molecular characteristics of cancer cells considering the circulating tumor cells (CTCs) that are deeply involved in distant metastasis [30,31]. One such report suggested CTCs to possibly be an indicator of the therapeutic effect of chemotherapy or endocrine therapy [32], whereas some other studies reported them as a predictor of distant metastatic recurrence of breast cancer based on clinical deta [33,34]. Some publications have even reported the prediction of distant metastasis using genetic assays [35].…”
Section: Discussionmentioning
confidence: 99%
“…There have also been reports that examined the molecular characteristics of cancer cells with respect to the circulating tumor cells (CTCs) that are deeply involved in distant metastasis [31,32]. One such report suggested that CTCs may be indicators of the therapeutic effect of chemotherapy or endocrine therapy [33], while other studies reported them to be predictors of distant metastatic recurrence of breast cancer based on clinical data [34,35]. A few publications have even reported the prediction of distant metastasis using genetic assays [36].…”
Section: Discussionmentioning
confidence: 99%